Extracellular Matrix Signals as Drivers of Mitochondrial Bioenergetics and Metabolic Plasticity of Cancer Cells During Metastasis - Urra, Félix A.; Fuentes-Retamal, Sebastián; Palominos, Charlotte; Rodríguez-Lucart, Yarcely A.; López-Torres, Camila; Araya-Maturana, Ramiro (Frontiers in Cell and Developmental Biology, 2021)
The role of metabolism in tumor growth and chemoresistance has received considerable attention, however, the contribution of mitochondrial bioenergetics in migration, invasion, and metastasis is recently being understood. Migrating cancer cells adapt their energy needs to fluctuating changes in the microenvironment, exhibiting high metabolic plasticity. This occurs due to dynamic changes in the contributions of metabolic pathways to promote localized ATP production in lamellipodia and control signaling mediated by mitochondrial reactive oxygen species. Recent evidence has shown that metabolic shifts toward a mitochondrial metabolism based on the reductive carboxylation, glutaminolysis, and phosphocreatine-creatine kinase pathways promote resistance to anoikis, migration, and invasion in cancer cells. The PGC1a-driven metabolic adaptations with increased electron transport chain activity and superoxide levels are essential for metastasis in several cancer models. Notably, these metabolic changes can be determined by the composition and density of the extracellular matrix (ECM). ECM stiffness, integrins, and small Rho GTPases promote mitochondrial fragmentation, mitochondrial localization in focal adhesion complexes, and metabolic plasticity, supporting enhanced migration and metastasis. Here, we discuss the role of ECM in regulating mitochondrial metabolism during migration and metastasis, highlighting the therapeutic potential of compounds affecting mitochondrial function and selectively block cancer cell migration.